Sniper 2 - Baxley, Craig R.; Kotternbrook, Carol; Entbinder, Scott (Tristar Pictures; distributed in the Philippines by MagnaVision, 2002)
Sergent Thomas Beckett is back - and this time he's teamed up with a death row inmate named B.J. Cole on a suicide mission to the Bal;kans. Their target: a rogue general accused of running a stealth operation of hit-and-run ethnic cleansing missions in an area known as "No Man's Land." But when Beckett discovers that the government is using him as a pawn in a bigger mission, the body count grows and bullets really start to fly!